Grandpa Green - Smith, Lane. (New York : Roaring Brook Press, 2011)
A child explores the ordinary life of his extraordinary great-grandfather, as expressed in his topiary garden.
Booklist
Pub Weekly
School Library Journal starred
Booklist, July 2011
Horn Book, September 2011
Kirkus Review, July 2011
Keywords: Gardens -- Juvenile fiction; Great-grandfathers -- Juvenile fiction; Gardens -- Fiction; Great-grandfathers -- Fiction; Gardens -- Fiction; Great-grandfathers -- Fiction; Picture books for children